“Myroslava” and “Khrystyna” drinking mineral waters modulate the state of neuroendocrine-immune complex and metabolism in patients of Truskavets’ spa - Gozhenko, Anatoliy; Hrytsak, Myroslava; Popovych, Dariya; Badiuk, Nataliya; Żukow, Xawery (Journal of Education, Health and Sport, 2022)
Background. Earlier in an experiment on rats we showed that newly created sulfate-chloride sodium-magnesium drinking mineral waters "Myroslava" and "Khrystyna" of Truskavets’ spa has a significant modulating effects on the parameters of metabolism and the autonomic nervous, endocrine and immune systems. Adhering to the principle "Ex experimento ad clinic", we continued research in this direction with the participation of patients of the resort. We showed that these mineral waters have favorable effects on metabolic, HRVs, EEGs, endocrine and immune parameters. This article presents an integrated assessment of previously identified effects. Materials and Methods. The object of clinical-physiological observation were 34 men aged 23-70 years, who underwent rehabilitation treatment of chronic cholecystitis and pyelonephritis in remission in the Truskavets’ spa. The examination was performed twice, before and after a 7-10-day course of balneotherapy. All patients received bioactive water Naftussya, however, 11 men additionally drank water "Khrystyna", and the other 11 men water "Myroslava". The subject of the study were the parameters of the neuroendocrine-immune complex and metabolism. Results. The complex balneotherapy by interval use of sulfate-chloride sodium-magnesium mineral waters with Naftusya water causes significant changes in the constellation of EEGs, HRVs, endocrine, metabolic and immune parameters, which are different from the effects of Naftusya water monotherapy. Own effects of mineral waters are estimated by modeling. In general, the effects are physiologically favorable and have a normalizing nature. Conclusion. The newly created sulfate-chloride sodium-magnesium drinking mineral waters of Truskavets’ spa have favorable neuroendocrine, metabolic and immune effects on patients with chronic cholecystitis and pyelonephritis.